Tingkat Pengetahuan Orang Tua dalam Meningkatkan Kesehatan Gigi dan Mulut pada Anak Usia 6-10 Tahun - Ahmad F Pulungan; Ainun Ayu Yuniar; Zilal Islamy Paramma; Nurul Safira Maulida (Jurnal Terapi Gigi dan Mulut, 2025)
The background of this study is based on the high prevalence of dental and oral health problems in children, with 60-90% of school-aged children experiencing tooth decay. Additionally, the active role of parents is crucial in guiding children to maintain good oral health. The objective of this study was to identify the level of parental knowledge in improving the oral health of children aged 6-10 years at the Hasanuddin University Dental and Oral Health Education Hospital. This research method used a cross-sectional design with a sample of 93 parents of children aged 6-10 years undergoing treatment at RSGMP. The results of the study showed that respondents who obtained scores in the range of 26-40 contributed 54.3% of the total respondents, indicating that more than half of the respondents were classified as good. Respondents who scored between 0 and 15 numbered 10 individuals, representing 1.1%, while those who scored between 16 and 26 numbered 40 individuals, accounting for 45.2% of the total 93 respondents, falling into the moderate score category. The study concluded that fathers were more dominant than mothers in actively maintaining their children's dental health. Respondents who obtained a good category contributed 54.3%, respondents in the poor category numbered 10, representing 1.1%, and respondents in the moderate category numbered 40, accounting for 45.2% of the total 93 respondents, who were parents of children at the RSGMP of Hasanuddin University.